D DINAMIKA KEKUASAAN, ISLAM DAN WARISAN BUDAYA DI BANJARNEGARA - Sofa Marwah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2019)
This study describe the dynamics of a power in Banjarnegara and to study Islam and its cultural heritage. Banjarnegara is located far from negarigung; hence, it does not become the focus study of experts. Nevertheless, Banjarnegara’s history and its culture are precious. This study is a library research based on many sources talked about Banjarnegara. The result shows that the power ruling in Banjarnegara is hereditary, but then, it has to fight against the colonial politics and higher power caused this hereditary is useless. The dynamics of a power in Banjarnegara also takes a part in developing Islam as the Walisanga ancestry are prominent figures in the area. Along with the power of Mataram, the palace gave the status of a perdikan in Kademangan Gumelem, as storage of palace’s heirlooms and burial of Islamic leaders in Banjarnegara. At this moment, Gumelem is the center of nyadran gede held by local government, a good way to fuse previous legacies and present authorities. Gumelem also bequeaths traditional batik as one of palace legacies.